1990
DOI: 10.1083/jcb.110.3.569
|View full text |Cite
|
Sign up to set email alerts
|

Core filaments of the nuclear matrix.

Abstract: Abstract. The nuclear matrix is concealed by a much larger mass of chromatin, which can be removed selectively by digesting nuclei with DNase I followed by elution of chromatin with 0.25 M ammonium sulfate. This mild procedure removes chromatin almost completely and preserves nuclear matrix morphology. The complete nuclear matrix consists of a nuclear lamina with an interior matrix composed of thick, polymorphic fibers and large masses that resemble remnant nucleoli. Further extraction of the nuclear matrices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
368
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(388 citation statements)
references
References 41 publications
19
368
1
Order By: Relevance
“…The latter is a complex network of nuclear proteins and RNA (He et al, 1990;Pederson, 1998). We found that RNase treatment of permeabilized nuclei releases p53, as can be seen in Figure 1d.…”
Section: P53 In Hep G2 Cellssupporting
confidence: 58%
“…The latter is a complex network of nuclear proteins and RNA (He et al, 1990;Pederson, 1998). We found that RNase treatment of permeabilized nuclei releases p53, as can be seen in Figure 1d.…”
Section: P53 In Hep G2 Cellssupporting
confidence: 58%
“…This treatment further removes the components that are dependent on complex formation with RNA (16). Counterstaining of slides with DAPI (as described above) was used to monitor completeness of chromatin extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Fractionation of cellular proteins was performed as described 55 with some modifications. HCT116 cells were extracted in cytoskeleton buffer (CSK) (10 mM Pipes pH 6.8, 100 mM NaCl, 300 mM sucrose, 3 mM MgCl 2 , 1 mM EGTA, 0.5% Triton X-100) supplemented with 1 mM dithiothreitol, protease inhibitors (Complete; Roche Diagnostics) and phosphatase inhibitors (Cocktail I; Sigma).…”
Section: Cellular Fractionationmentioning
confidence: 99%